Profitability Identification of National Banking through Credit, Capital, Capital Structure, Efficiency, and Risk Level - Sugeng Haryanto (Jurnal Dinamika Manajemen)
This study aims to analyze the influence of credit, bank capital, capital structure, efficiency and risk toward the profitability in banking industry. Bank has an important role in the economy in Indonesia in 2014. The purposive sampling technique was used in this study to filter the samples according to several criteria such as being public at least in 2008, and publicly released the financial statement from 2008-2013. The total sample of 25 banks. Multiple regression technique was used in this study to analyze the data. The results show that credit, bank capital, and capital structure positively influence the profitability. This result supported by the previous research. The other finding shows that efficiency and risk have significantly negative effect on profitability. Bangking has an 80 percent market share in the financing of intermediation function of the entire financial system.